Expanding the Inventory of Molecule-rich Planetary Nebulae: New Observations of M4-17, Hu 1-1, M1-59, and Na 2 - K. R. Gold; D. R. Schmidt; L. M. Ziurys (The Astrophysical Journal)
Molecular observations of four planetary nebulae (PNe), M4-17, Hu 1-1, M1-59, and Na 2, were conducted at 1–3 mm using the Arizona Radio Observatory’s 12 m antenna and Submillimeter Telescope, and the Institut de Radioastronomie Millimétrique 30 m Telescope. Toward M4-17, HNC ( J = 3 → 2), CCH ( N = 2 → 1, N = 3 → 2), CN ( N = 1 → 0, N = 2 → 1), H _2 CO ( J _Ka,Kc = 2 _1,2 → 1 _1,1 , J _Ka,Kc = 2 _0,2 → 1 _0,1 , J _Ka,Kc = 2 _1,1 → 1 _1,0 ), CS ( J = 3 → 2, J = 5 → 4), and H ^13 CN ( J = 2 → 1) were detected. An almost identical set of transitions was identified toward Hu 1-1. Moreover, c–C _3 H _2 was detected in Hu 1-1 via three 2 mm lines: J _Ka,Kc = 3 _1,2 → 2 _2,1 , J _Ka,Kc = 4 _1,4 → 3 _0,3 , and J _Ka,Kc = 3 _2, 2 → 2 _1,1 . HNC, CCH, CN, CS, and H ^13 CN were found in M1-59, as well as H _2 S via its J _Ka,Kc = 1 _1,0 → 1 _0,1 line—the first detection of this key sulfur species in PNe. In addition, CCH and CN were identified in the 27,000 yr old Na 2. Among these four sources, CN and CCH were the most prevalent molecules (after CO and H _2 ) with fractional abundances, relative to H _2 , of f ∼ 0.9–7.5 × 10 ^−7 and 0.8–7.5 × 10 ^−7 , respectively. CS and HNC have abundances in the range f ∼ 0.5–5 × 10 ^−8 , the latter resulting in HCN/HNC ∼ 3 across all three PNe. The unusual species H _2 CO, c–C _3 H _2 , and H _2 S had f ∼ 3–4 × 10 ^−7 , 10 ^−8 , and 6 × 10 ^−8 . This study suggests that elliptical PNe such as Hu 1-1 can have a diverse molecular composition. The presence of CN, CCH, and HCO ^+ in Na 2, with comparable abundances to younger PNe, demonstrates that molecular content is maintained into the late PN stage.